Curcumin, a Natural Antimicrobial Agent with Strain-Specific Activity - Artur Adamczak; Marcin Ożarowski; Tomasz M. Karpiński (MDPI AG, 2020)
Curcumin, a principal bioactive substance of turmeric (Curcuma longa L.), is reported as a strong antioxidant, anti-inflammatory, antibacterial, antifungal, and antiviral agent. However, its antimicrobial properties require further detailed investigations into clinical and multidrug-resistant (MDR) isolates. In this work, we tested curcumin's efficacy against over 100 strains of pathogens belonging to 19 species. This activity was determined by the broth microdilution method and by calculating the minimum inhibitory concentration (MIC). Our findings confirmed a much greater sensitivity of Gram-positive than Gram-negative bacteria. This study exhibited a significantly larger variation in the curcumin activity than previous works and suggested that numerous clinical strains of widespread pathogens have a poor sensitivity to curcumin. Similarly, the MICs of the MDR types of Staphylococcus aureus, S. haemolyticus, Escherichia coli, and Proteus mirabilis were high (≥2000 µg/mL). However, curcumin was effective against some species and strains: Streptococcus pyogenes (median MIC = 31.25 µg/mL), methicillin-sensitive S. aureus (250 µg/mL), Acinetobacter lwoffii (250 µg/mL), and individual strains of Enterococcus faecalis and Pseudomonas aeruginosa (62.5 µg/mL). The sensitivity of species was not associated with its affiliation to the genus, and it could differ a lot (e.g., S. pyogenes, S. agalactiae and A. lwoffii, A. baumannii). Hence, curcumin can be considered as a promising antibacterial agent, but with a very selective activity.